2003
DOI: 10.1002/bies.10225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of aging in the fly: Is this the end of the beginning?

Abstract: How we age and what we can do about it have been uppermost in human thought since antiquity. The many false starts have frustrated experimentalists and theoretical arguments pronouncing the inevitability of the process have created a nihilistic climate among scientists and the public. The identification of single gene alterations that substantially extend life span in nematodes and flies however, have begun to reinvigorate the field. Drosophila's long history of contributions to aging research, rich storehouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…Decreases in physical activity, reproductive status (especially in females), or calorie intake are known to increase life span in the fly (reviewed in ref. 33). Although we did not perform quantitative studies, visual inspection suggested no obvious decrease in physical activity or fertility in the long-lived dSir2-overexpressing flies compared with their matched controls.…”
Section: Increasing Sir2 Expression In Neurons Extends Life Spanmentioning
confidence: 99%
“…Decreases in physical activity, reproductive status (especially in females), or calorie intake are known to increase life span in the fly (reviewed in ref. 33). Although we did not perform quantitative studies, visual inspection suggested no obvious decrease in physical activity or fertility in the long-lived dSir2-overexpressing flies compared with their matched controls.…”
Section: Increasing Sir2 Expression In Neurons Extends Life Spanmentioning
confidence: 99%
“…The involvement of ROS in limiting lifespan has been suggested by analyses of transgenic Drosophila, which systematically overexpress both Sod and Cat genes. Some strains of these transgenic flies live up to 30% longer than their natural counterparts, whereas flies carrying only one of these constitutively expressed transgenes do not live longer, suggesting that ROS tox-icity plays an important role in longevity (20,21).…”
Section: Ros Telomeres and Agingmentioning
confidence: 99%
“…It is likely that this first wave of loss is due to direct differentiation of the GSCs without selfrenewing divisions. However, a significant 30% decrease in the number of GSCs is observed in 30-day-old wild type males [33,34]; the median lifespan of a wild type laboratory strain of Drosophila melanogaster is 40 days [36]. The trend continues with a nearly 40% decrease in the number of GSCs by 50 days [34].…”
Section: Effects Of Aging On Germline Stem Cell Number and Activity Imentioning
confidence: 90%